RICE EXTRACT-ASSISTED GREEN SYNTHESIS OF Au NANOPARTICLES: CATALYTIC AND SERS ACTIVITIES - Singh M.K.; Verma A.; Basu J.; Sinha I.; Chettri P.; Tripathi A.; Tiwari A.; Mandal R.K. (My University, 2025)
In this paper, we investigate the impact of rice-starch stabilization of gold nanoparticles (AuNPs) on their catalytic and surface-enhanced Raman spectroscopy (SERS) activities. A typical green synthesis protocol was used to prepare AuNPs with rice-starch functioning as the reductant and the stabilizer. The localized surface plasmon resonance (LSPR) of the starch-stabilized AuNPs is pH-sensitive and got red-shifted with the medium's pH. The average size of the AuNPs formed decreased with the amount of rice-starch up to a certain level. TEM result shows that the polymeric behavior of starch extract may help synthesize the Au nanorod morphologies. AuNPs stabilized by different amounts of rice-starch were applied as the catalysts for the model p-nitrophenol reduction reaction. For all AuNP catalysts used, the reaction followed pseudo-first-order kinetics. The catalyst turnover frequencies increased up to a certain level of starch functionalization. Further increase in starch led to a fall in the activity of AuNPs catalyst. The evidence on rate kinetics, induction times, activation energies, and turnover frequencies is combined to explain this phenomenon in terms of starch content. The SERS response of these AuNPs as substrates has also been investigated for methylene blue as the target molecules. AuNP substrates with an excess amount of starch weaken the SERS response and it can be ascribed to decreased light scattering efficiency of NPs as well as reduced interactions of methylene blue molecules with the NP surface. © 2022 World Scientific Publishing Company.